#16: Use of a Multiplex PCR Panel for Diagnosis of Complicated Pneumonia in Pediatrics. (26th March 2021) - Armas, Elisa A; Melgar, M; Juárez, J; Vidal, M; Eguizábal, J; Gordillo, R
Abstract: Background: Pleural fluid cultures performed in the period from April 2015 to April 2017 (prior to having the test) were reviewed, 120 cultures were found, of which 7.5% were positive. Methods: Descriptive study in patients from 0 to 12 years old, from April 2017 to April 2019, at Roosevelt Hospital, Guatemala City, June 2019 Results: In the period from April 2017 to April 2019, pleural fluids were evaluated in which multiplex PCR was performed, obtaining 41 results, 24 positive PCR for pneumonia producing bacteria in the community, of which only 1 positive culture was found, which, if correlated, which means 25 times more detection capacity, than the Gold standard of culture. Forty-one cultures of pleural fluids were evaluated, of which 58% were detected by FilmArray® The most frequently isolated microorganisms were Streptococcus pneumoniae 42%, Streptococcus sp. 3% Haemophilus influenzae 13% and Pseudomonas aeruginosa 3% Conclusion: The use of Multiplex PCR in pleural fluid allowed the identification of a high percentage of microorganisms in the pleural fluid. Although the test is not valid for this use, its use could mean a great advantage for the etiological diagnosis.